2022
DOI: 10.1007/s16024-022-00389-9
|View full text |Cite
|
Sign up to set email alerts
|

Die MISSCARE-Austria-Studie – Teil II

Abstract: Zusammenfassung Hintergrund Eine sichere und qualitativ angemessene Versorgung im Krankenhaus erfordert den Einsatz einer adäquaten, den Bedarfen von Patient*innen und ihrer Angehörigen entsprechenden Anzahl an qualifizierten Pflegepersonen. Für Allgemeinstationen in österreichischen Krankenhäusern gibt es hierzu keine explizite Orientierung. Die Datenlage zum Pflegepersonaleinsatz auf Allgemeinstationen und dessen Angemessenheit ist hierzulande limitiert. Diese beiden Faktoren dien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…3. Considering sampling assumptions, we point out, that our sample consisted of a pseudo-probabilistic sample and was deemed representative for Austrian Nurses working in general medical and surgical units regarding the following characteristics: geographical distribution across regional provinces, number of working hours per week, gender and role (Cartaxo et al, 2022a(Cartaxo et al, , 2022b(Cartaxo et al, , 2022c. Regarding the sample size, Muthén and Muthén (2002) suggests a minimum of 300 participants, when we lead with non-normal distributed data.…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Considering sampling assumptions, we point out, that our sample consisted of a pseudo-probabilistic sample and was deemed representative for Austrian Nurses working in general medical and surgical units regarding the following characteristics: geographical distribution across regional provinces, number of working hours per week, gender and role (Cartaxo et al, 2022a(Cartaxo et al, , 2022b(Cartaxo et al, , 2022c. Regarding the sample size, Muthén and Muthén (2002) suggests a minimum of 300 participants, when we lead with non-normal distributed data.…”
Section: Assumptionsmentioning
confidence: 99%
“…According to (Bentler, 2011), conducting SEM requires the consideration of set of assumptions, which aim to secure the validity and rigour of this approach: “major assumptions associated with structural equation modeling include multivariate normality, no systematic missing data, sufficiently large sample size, and correct model specification” (p. 15,218): Because a severe violation of multivariate normality is expected in this type of data, we recurred to diagonal weighted least squares robust estimators (DWLS) as means of parameter estimation, which is also adequate for ordinal data (Muthén et al, 1997). Only cases with complete data were considered for SEM. Considering sampling assumptions, we point out, that our sample consisted of a pseudo ‐probabilistic sample and was deemed representative for Austrian Nurses working in general medical and surgical units regarding the following characteristics: geographical distribution across regional provinces, number of working hours per week, gender and role (Cartaxo et al, 2022a, 2022b, 2022c). Regarding the sample size, Muthén and Muthén (2002) suggests a minimum of 300 participants, when we lead with non‐normal distributed data.…”
Section: The Studymentioning
confidence: 99%
“…Cartaxo et al investigated general wards of Austrian hospitals, defining the ratio of nursing staff to patients as a patient-to-nurse ratio (PtN) value. Their study revealed that, on average, one nurse was responsible for 18.4 patients, leading to the conclusion that the staffing was deemed inappropriate [19].…”
Section: Introductionmentioning
confidence: 99%